Learning and speaking Filipino - Perdon, Renato. 4 0 16; 5 (Sydney/Manila : Manila Prints, 2008)
Filipino language book intended for travelers/tourist visiting the Philippines.
Includes bibliographical references.
English and Tagalog.
Keywords: 2 -- 0; 6; 20; 20; 2